The need for European harmonization of Nutrivigilance in a public health perspective: a comprehensive review - G. Vo Van Regnault; M. C. Costa; A. Adanić Pajić; A. P. Bico; S. Bischofova; U. Blaznik; F. Menniti-Ippolito; K. Pilegaard; C. Rodrigues; I. Margaritis (Critical Reviews in Food Science and Nutrition, 2022)

Soil respiration is stimulated by elevated CO 2 and reduced by summer drought: three years of measurements in a multifactor ecosystem manipulation experiment in a temperate heathland (CLIMAITE) - Merete B. Selsted; Leon van der Linden; Andreas Ibrom; Anders Michelsen; Klaus S. Larsen; Jane K. Pedersen; Teis N. Mikkelsen; Kim Pilegaard; Claus Beier; Per Ambus (Global Change Biology, 2012)
This study investigated the impact of predicted future climatic and atmospheric conditions on soil respiration ( R S ) in a Danish Calluna‐Deschampsia‐ heathland. A fully factorial in situ experiment with treatments of elevated atmospheric CO 2 (+130 ppm), raised soil temperature (+0.4 °C) and extended summer drought (5–8% precipitation exclusion) was established in 2005. The average R S , observed in the control over 3 years of measurements (1.7 μmol CO 2 m −2 sec −1 ), increased 38% under elevated CO 2 , irrespective of combination with the drought or temperature treatments. In contrast, extended summer drought decreased R S by 14%, while elevated soil temperature did not affect R S overall. A significant interaction between elevated temperature and drought resulted in further reduction of R S when these treatments were combined. A detailed analysis of short‐term R S dynamics associated with drought periods showed that R S was reduced by ~50% and was strongly correlated with soil moisture during these events. Recovery of R S to pre‐drought levels occurred within 2 weeks of rewetting; however, unexpected drought effects were observed several months after summer drought treatment in 2 of the 3 years, possibly due to reduced plant growth or changes in soil water holding capacity. An empirical model that predicts R S from soil temperature, soil moisture and plant biomass was developed and accounted for 55% of the observed variability in R S . The model predicted annual sums of R S in 2006 and 2007, in the control, were 672 and 719 g C m −2 y −1 , respectively. For the full treatment combination, i.e. the future climate scenario, the model predicted that soil respiratory C losses would increase by ~21% (140–150 g C m −2 y −1 ). Therefore, in the future climate, stimulation of C storage in plant biomass and litter must be in excess of 21% for this ecosystem to not suffer a reduction in net ecosystem exchange.

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

Reduction of ecosystem productivity and respiration during the European summer 2003 climate anomaly: a joint flux tower, remote sensing and modelling analysis - M. REICHSTEIN; P. CIAIS; D. PAPALE; R. VALENTINI; S. RUNNING; N. VIOVY; W. CRAMER; A. GRANIER; J. OGÉE; V. ALLARD; M. AUBINET; Chr. BERNHOFER; et al. (Global Change Biology, 2007)
The European CARBOEUROPE/FLUXNET monitoring sites, spatial remote sensing observations via the EOS‐MODIS sensor and ecosystem modelling provide independent and complementary views on the effect of the 2003 heatwave on the European biosphere's productivity and carbon balance. In our analysis, these data streams consistently demonstrate a strong negative anomaly of the primary productivity during the summer of 2003. FLUXNET eddy‐covariance data indicate that the drop in productivity was not primarily caused by high temperatures (‘heat stress’) but rather by limitation of water (drought stress) and that, contrary to the classical expectation about a heat wave, not only gross primary productivity but also ecosystem respiration declined by up to more than to 80 gC m −2 month −1 . Anomalies of carbon and water fluxes were strongly correlated. While there are large between‐site differences in water‐use efficiency (WUE, 1–6 kg C kg −1 H 2 O) here defined as gross carbon uptake divided by evapotranspiration (WUE=GPP/ET), the year‐to‐year changes in WUE were small ( −1 ) and quite similar for most sites (i.e. WUE decreased during the year of the heatwave). Remote sensing data from MODIS and AVHRR both indicate a strong negative anomaly of the fraction of absorbed photosynthetically active radiation in summer 2003, at more than five standard deviations of the previous years. The spatial differentiation of this anomaly follows climatic and land‐use patterns: Largest anomalies occur in the centre of the meteorological anomaly (central Western Europe) and in areas dominated by crops or grassland. A preliminary model intercomparison along a gradient from data‐oriented models to process‐oriented models indicates that all approaches are similarly describing the spatial pattern of ecosystem sensitivity to the climatic 2003 event with major exceptions in the Alps and parts of Eastern Europe, but differed with respect to their interannual variability.

Predicting the onset of net carbon uptake by deciduous forests with soil temperature and climate data: a synthesis of FLUXNET data - Dennis D. Baldocchi; T. A. Black; P. S. Curtis; E. Falge; J. D. Fuentes; A. Granier; L. Gu; A. Knohl; K. Pilegaard; H. P. Schmid; R. Valentini; K. Wilson; et al. (International Journal of Biometeorology, 2005)

Pan‐European δ 13 C values of air and organic matter from forest ecosystems - Deborah Hemming; Dan Yakir; Per Ambus; Mika Aurela; Cathy Besson; Kevin Black; Nina Buchmann; Regis Burlett; Alessandro Cescatti; Robert Clement; Patrick Gross; André Granier; et al. (Global Change Biology, 2005)
We present carbon stable isotope, δ 13 C, results from air and organic matter samples collected during 98 individual field campaigns across a network of Carboeuroflux forest sites in 2001 (14 sites) and 2002 (16 sites). Using these data, we tested the hypothesis that δ 13 C values derived from large‐scale atmospheric measurements and models, which are routinely used to partition carbon fluxes between land and ocean, and potentially between respiration and photosynthesis on land, are consistent with directly measured ecosystem‐scale δ 13 C values. In this framework, we also tested the potential of δ 13 C in canopy air and plant organic matter to record regional‐scale ecophysiological patterns. Our network estimates for the mean δ 13 C of ecosystem respired CO 2 and the related ‘discrimination’ of ecosystem respiration, δ er and Δ er , respectively, were −25.6±1.9‰ and 17.8 ±2.0‰ in 2001 and −26.6±1.5‰ and 19.0±1.6‰ in 2002. The results were in close agreement with δ 13 C values derived from regional‐scale atmospheric measurement programs for 2001, but less so in 2002, which had an unusual precipitation pattern. This suggests that regional‐scale atmospheric sampling programs generally capture ecosystem δ 13 C signals over Europe, but may be limited in capturing some of the interannual variations. In 2001, but less so in 2002, there were discernable longitudinal and seasonal trends in δ er . From west to east, across the network, there was a general enrichment in 13 C (∼3‰ and ∼1‰ for the 2 years, respectively) consistent with increasing Gorczynski continentality index for warmer and drier conditions. In 2001 only, seasonal 13 C enrichment between July and September, followed by depletion in November (from about −26.0‰ to −24.5‰ to −30.0‰), was also observed. In 2001, July and August δ er values across the network were significantly related to average daytime vapor pressure deficit (VPD), relative humidity (RH), and, to a lesser degree, air temperature ( T a ), but not significantly with monthly average precipitation ( P m ). In contrast, in 2002 (a much wetter peak season), δ er was significantly related with T a , but not significantly with VPD and RH. The important role of plant physiological processes on δ er in 2001 was emphasized by a relatively rapid turnover (between 1 and 6 days) of assimilated carbon inferred from time‐lag analyses of δ er vs. meteorological parameters. However, this was not evident in 2002. These analyses also noted corresponding diurnal cycles of δ er and meteorological parameters in 2001, indicating a rapid transmission of daytime meteorology, via physiological responses, to the δ er signal during this season. Organic matter δ 13 C results showed progressive 13 C enrichment from leaves, through stems and roots to soil organic matter, which may be explained by 13 C fractionation during respiration. This enrichment was species dependent and was prominent in angiosperms but not in gymnosperms. δ 13 C values of organic matter of any of the plant components did not well represent short‐term δ er values during the seasonal cycle, and could not be used to partition ecosystem respiration into autotrophic and heterotrophic components.

Assessment of CH4 and N2O fluxes in a Danish beech (Fagus sylvatica) forest and an adjacent N-fertilised barley (Hordeum vulgare) field: effects of sewage sludge amendments - P. Ambus; J.M. Jensen; A. Priemé; K. Pilegaard; A. Kjøller (Nutrient Cycling in Agroecosystems, 2001)

Productivity overshadows temperature in determining soil and ecosystem respiration across European forests - I. A. Janssens; H. Lankreijer; G. Matteucci; A. S. Kowalski; N. Buchmann; D. Epron; K. Pilegaard; W. Kutsch; B. Longdoz; T. Grünwald; L. Montagnani; S. Dore; et al. (Global Change Biology, 2001)
Summary This paper presents CO 2 flux data from 18 forest ecosystems, studied in the European Union funded EUROFLUX project. Overall, mean annual gross primary productivity (GPP, the total amount of carbon (C) fixed during photosynthesis) of these forests was 1380 ± 330 gC m −2 y −1 (mean ±SD). On average, 80% of GPP was respired by autotrophs and heterotrophs and released back into the atmosphere (total ecosystem respiration, TER = 1100 ± 260 gC m −2 y −1 ). Mean annual soil respiration (SR) was 760 ± 340 gC m −2 y −1 (55% of GPP and 69% of TER). Among the investigated forests, large differences were observed in annual SR and TER that were not correlated with mean annual temperature. However, a significant correlation was observed between annual SR and TER and GPP among the relatively undisturbed forests. On the assumption that (i) root respiration is constrained by the allocation of photosynthates to the roots, which is coupled to productivity, and that (ii) the largest fraction of heterotrophic soil respiration originates from decomposition of young organic matter (leaves, fine roots), whose availability also depends on primary productivity, it is hypothesized that differences in SR among forests are likely to depend more on productivity than on temperature. At sites where soil disturbance has occurred (e.g. ploughing, drainage), soil espiration was a larger component of the ecosystem C budget and deviated from the relationship between annual SR (and TER) and GPP observed among the less‐disturbed forests. At one particular forest, carbon losses from the soil were so large, that in some years the site became a net source of carbon to the atmosphere. Excluding the disturbed sites from the present analysis reduced mean SR to 660 ± 290 gC m −2 y −1 , representing 49% of GPP and 63% of TER in the relatively undisturbed forest ecosystems.

Consistency of motor-unit identification during force-varying static contractions - M. Pilegaard; B. R. Jensen; G. Sjgaard; K. Sgaard (European Journal of Applied Physiology, 2000)

First-Order Chemistry in the Surface-Flux Layer - L. Kristensen; C. E. Andersen; H. E. Jørgensen; P. Kirkegaard; K. Pilegaard (Journal of Atmospheric Chemistry, 1997)